2018
DOI: 10.1097/inf.0000000000001760
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Drug Resistance Prevalence, HIV-1 Variants and Clinical Status in HIV-1-infected Pediatric Population in Madrid: 1993 to 2015 Analysis

Abstract: Periodic surveillance resistance and molecular epidemiology studies in long-term pretreated HIV-infected pediatric populations are required to optimize treatment regimens. Results will permit a better understanding of long-time dynamics of viral resistance and HIV-1 variants in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…This high rate was coincident with the rate of ADR among autochthonous Portuguese patients (62%). Other European studies have revealed a high rate of ADR around 64% [42,43]. This ADR rate in migrants probably reflects long term follow up in portuguese hospitals and, therefore, is similar to autochtonous patients followed up in the same hospital.…”
Section: Discussionsupporting
confidence: 57%
“…This high rate was coincident with the rate of ADR among autochthonous Portuguese patients (62%). Other European studies have revealed a high rate of ADR around 64% [42,43]. This ADR rate in migrants probably reflects long term follow up in portuguese hospitals and, therefore, is similar to autochtonous patients followed up in the same hospital.…”
Section: Discussionsupporting
confidence: 57%
“…Among them, 203 (97.6%) could be successfully subtyped by phy. Overall, 172 (83.9%) of the 205 HIV-1 subjects were infected with HIV-1 subtype B pol , being the predominant variant, as previously reported 9,10 . HIV-1 subtype B infections were more frequent than by non-B variants (83.9% vs. 16.1%; p < 0.0001) in the whole cohort.…”
supporting
confidence: 72%
“…For resistance testing and HIV-1 variant characterization we selected the sequence/profile closest to December 2017 per patient, defining as sampling time the year of collection of sequenced samples, which ranged from 1993 to 2017. Most sequences were previously reported by our group 9 , 10 , except 20 new pol genotypes recovered from hospitals. We also collected retrospective epidemiological-virological data from clinical records closest to December 2017: origin, gender, age, HIV transmission route, HIV diagnosis date, antiretroviral therapy (ART) experience, CD4 and CD8 counts (percentage and cells/mm 3 ), CD4/CD8 rate, and viral load (HIV- 1 RNA copies/ml of plasma, cp/ml).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, information on the frequency and severity of long‐term adverse effects in children is limited 89 . Periodic surveillance studies and molecular epidemiology are required in long‐term pretreated HIV‐infected paediatric populations to optimize treatment regimens and to better understand the long‐term dynamics of viral resistance and variants of HIV 117 …”
Section: Viral Infections and Mitochondrial Involvementmentioning
confidence: 99%